Faktor-Faktor Yang Mempengaruhi Cadangan Devisa Di Indonesia - Savira, Nadya Pambudianing; Zafrizal, Meliza (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
Foreign exchange reserves become a measure of wealth for a country. Foreign exchange is used to finance various national development initiatives. In 2022, the country with the 3rd largest foreign exchange reserves in ASEAN is Indonesia. This study analyzes the relationship between inflation, interest rates, exports, and foreign debt as independent variables and foreign exchange reserves as dependent variables in Indonesia using time series data from 2015-2023 in the form of monthly data. Multiple regression analysis is applied as an analysis technique. Based on the studies that have been conducted, the study findings partially state that foreign exchange reserves are not significantly affected by interest rates, inflation, and exports. However, partial external debt is significant to foreign exchange reserves. However, the researchers recommend that other researchers can continue with differences and novelty in scientific thinking and are expected to include other variables such as the number of countries, years of research, and the study of more theories.